Perceptions and adaptation strategies of smallholder farmers to climate change in Builsa South district of Ghana - John Adeboa; Benjamin Tetteh Anang (Cogent Social Sciences, 2024)
Climate change (CC) poses a significant threat to small-scale farmers in low-income countries, increasing vulnerability to food insecurity and requiring various methods to mitigate its impact. The current study assessed producers’ perceptions of CC and the adaption measures they adopt to mitigate the effect of CC in Builsa South district of Ghana. A generalized Poisson regression model was used to evaluate the factors affecting adoption of climate change adaptation strategies (CCASs) by the respondents. Farmers’ knowledge of the factors contributing to CC was analyzed by employing a 5-point Likert scale while producers’ perception of the effect of CC on maize cultivation was assessed using Kendell’s coefficient of concordance. The findings indicated that deforestation, bush burning, improper disposal of waste and greenhouse gases are the main activities contributing to CC in the district. The adaptation strategies used by farmers include early planting, adoption of disease resistant and drought-tolerant varieties, crop rotation, mixed cropping, and zero tillage. The study further revealed that years of education, farm size, radio ownership, and crop insurance significantly enhanced adoption of CCASs. The authors recommend more education and training on CC adaptation practices to equip farmers with the skills to alleviate the impact of CC.